Recovering the Craft of Public Administration - Rhodes, Roderick A. W. (Public administration review, 2016)
Public sector reform has rarely dropped off the political agenda of Western governments, yet the old craft skills of traditional public administration remain of paramount importance. The pendulum has swung too far toward the new and the fashionable reforms associated with New Public Management and the New Public Governance. It needs to swing back toward bureaucracy and the traditional skills of bureaucrats as part of the repertoire of governing. This article discusses the skills of counseling, stewardship, practical wisdom, probity, judgment, diplomacy, and political nous. Although these skills are of wide relevance, the article focuses on their relevance in Australia, Britain, Canada, and New Zealand. It concludes that the next bout of reforms needs to recover the traditional craft skills. It is not a question of traditional skills versus the new skills of New Public Management or New Public Governance; it is a question of what works, of what skills fit in a particular context.